2012
DOI: 10.1186/1472-6963-12-27
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic status and traditional chinese medicine use among children in Taiwan

Abstract: BackgroundTraditional Chinese medicine (TCM) utilization is common in Asian countries. Limited studies are available on the socioeconomic status (SES) associated with TCM use among the pediatric population. We report on the association between SES and TCM use among children and adolescents in Taiwan.MethodsA National Health Interview Survey was conducted in Taiwan in 2001 that included 5,971 children and adolescents. We assessed the children's SES using the head of household's education, occupation and income.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
3
16
1
Order By: Relevance
“…As a result, out-of-pocket items of complementary healthcare have become obstacles for low-income patients. The present study revealed that higher economic status was associated with TCM use, which is consistent with the ndings of previous research [20].…”
Section: Tcm Is Widely Used In Taiwan and Other Asian Countries As Psupporting
confidence: 93%
“…As a result, out-of-pocket items of complementary healthcare have become obstacles for low-income patients. The present study revealed that higher economic status was associated with TCM use, which is consistent with the ndings of previous research [20].…”
Section: Tcm Is Widely Used In Taiwan and Other Asian Countries As Psupporting
confidence: 93%
“…Children with high SES also had the highest TCM utilization, and this may be because the behavior of seeking medical service and the SES of children are both related to their parents. [ 32 ] Recently, the rise in TCM utilization by people with high SES could result from belief in TCM and using TCM as an adjunct to WM as well as expectation of better quality of life and improvement of constitution through supplementary TCM treatment. [ 10 , 22 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the factors associated with TCM uses in Taiwan have found that people living in rural areas are less likely to access various conventional or unconventional therapies [28,36,37]. Second, the socioeconomic status (SES) of these individuals is usually low and low SES has been reported to be associated with low TCM use [38]. …”
Section: Discussionmentioning
confidence: 99%